Textile waste pre-treatments for enhanced chemical recycling - Cecília Ribeiro; Diana Sofia Pinto; Ana Francisca Miranda; João Seixas; Marcelo Oliveira; Catarina Costa (Discover Applied Sciences)
Abstract Textile waste recycling faces significant challenges due to contaminants that remain on the fibers, interfering with recovery processes regardless of the method used. In chemical recycling, the original finishing additives present in textiles can disrupt secondary reactions, making a pre-treatment step essential for impurity removal and chemical recycling process optimization. This study explores effective pre-treatment methods for the chemical recycling of cotton (CO) and polyester-cotton blends (PES-CO/CO-PES), focusing on approaches that balance efficiency and sustainability. An alkaline pre-treatment was used for decolorizing the samples, with ISO brightness measured, showing PES-CO achieving the best result (80.6%). As an innovation, process optimization was carried out by introducing an additive that allowed a 50% reduction in the amount of Na2S2O4 required while maintaining decolorization efficiency. This modification enhances process sustainability by reducing the consumption of chemical reagents. Additionally, an acid treatment with nitric acid was applied after the alkaline treatment to remove residual metals that could interfere with chemical recycling. This step proved highly beneficial, not only improving the purity of recycled materials but also increasing ISO brightness in all analyzed samples. Another crucial factor assessed was the degree of polymerization (DPv), which determines the material’s suitability for further recycling processes. Results showed a slight decrease in DPv throughout the treatments, indicating that despite the effective removal of dyes and contaminants, the structural integrity of the fibers was preserved, ensuring high-quality recycled material.